1995
DOI: 10.1007/bf00194099
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus: immunopathogenesis of neurologic dysfunction

Abstract: Neurologic complications of systemic lupus erythematosus (neuro-SLE) are common. The most frequent manifestations of neuro-SLE are seizures, encephalopathy, and behavioral changes, but a wide variety of other neurologic abnormalities affecting the central and peripheral nervous system and muscle also occur. Although the prevalence of neuro-SLE is high, the diversity of clinical presentations, the multiple potential etiologies, and the absence of sensitive and specific diagnostic tests render diagnosis difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Indeed, it is known that in SLE, the main disease associated to secondary APS, there are multiple causes for seizures, such as nervous central system activity, vasculitis, stroke, and meningoencephalitis [9, 30]. Moreover, all selected patients were negative for lupus-specific autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that in SLE, the main disease associated to secondary APS, there are multiple causes for seizures, such as nervous central system activity, vasculitis, stroke, and meningoencephalitis [9, 30]. Moreover, all selected patients were negative for lupus-specific autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that immune complexes, autoantibodies, and cytokines cause neurological disorders in SLE with direct effects and that vasculopathy developing in arterioles that feed the basal ganglia, coagulopathy, and bleeding disorders cause neurological disorders with indirect effects (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease that affects every organ and system in the body. The loss of tolerance in the immune system results in autoantibody production, immune complex deposition, and complement activation, which lead to systemic inflammation and target tissue damage ( 1 ). Genetic factors are essential in SLE susceptibility, according to family studies and the concordance rate between twins ( 2 ).…”
Section: Introductionmentioning
confidence: 99%